Isolation and Characterization of a Subsurface Bacterium Capable of Growth on Toluene, Naphthalene, and Other Aromatic Compounds - Fredrickson, J. K. (1991)
A bacterium, designated F199, utilized toluene, naphthalene, dibenzothiophene, salicylate, benzoate, p-cresol, and all isomers of xylene as a sole carbon and energy source. This bacterium was isolated from Middendorf sediments, a Cretaceous age formation that underlies the Southeast Coastal Plain in South Carolina, at a depth of approximately 410 m. F199 is a gram-positive, irregular-shaped bacterium that has a varied cell morphology that is dependent on culture medium type and growth stage. F199 required microaerobic conditions (40 to 80 μM O(2)) for growth on hydrocarbons, glucose, acetate, and lactate in mineral salts medium but not for growth on rich media. [(14)C]naphthalene mineralization by F199 was induced by either naphthalene or toulene; however, [(14)C]toluene mineralization by this strain was induced by toluene but not naphthalene. F199 was also found to harbor two plasmids larger than 100 kb. Restricted F199 plasmid and genomic DNA did not hybridize with toluene (pWW0) or naphthalene (NAH7) catabolic plasmid DNA probes. The presence in the Middendorf formation of bacteria with the capacity for degrading a variety of aromatic compounds suggests that indigenous microorganisms may have potential for in situ degradation of organic contaminants.